Land capability assessment for land use planning in West Tripura District, Northeast India with an integrated AHP-MCDA approach - KAUSIK PANJA; Y. V. KRISHNAIAH; DEBASIS DAS; MOUMITA HATI; VAJANA MONDAL; ATOSHI CHAKMA (Smujo International, 2026)
Abstract. Panja K, Krishnaiah YV, Das D, Hati M, Mondal V, Chakma A. 2026. Land capability assessment for land use planning in West Tripura District, Northeast India with an integrated AHP-MCDA approach. Asian J Agric 10 (1): g100114. https://doi.org/10.13057/asianjagric/g100114. Land capability assessment is essential for evaluating land resources, revealing the strengths and limitations of land utilization, and addressing problems of land encroachment, land degradation, deforestation, and food security. In West Tripura, Northeast India, rapid urbanization and changing agricultural practices have inadvertently altered the landscape, impacting the livelihoods of local people. Proper land use planning based on land capability is needed to address land-related issues. The primary objective of this study is to analyze the land capability of the district and identify specialized land capability zones to plan for future land use through conscious utilization of the district's natural resources. In this study, USDA land capability classification was derived from soil texture, lithology, soil depth, soil fragments, slope, elevation, drainage density, rainfall, soil moisture, soil pH, land use and land cover, groundwater potential, and temperature. These factors were considered as basic parameters for evaluating land capability in this hilly region. Analytic Hierarchy Process (AHP) techniques were used as part of multi-criteria decision analysis, and weighted overlay analysis was performed through Geographic Information System (GIS) to identify potential Land Capability Classes (LCC) in the district. The present study identified seven land capability classes. Land areas in the riverine plains and lunga (intermontane valley) areas were categorized as very good (Class I), good (Class II), moderately good (Class III), and fair (Class IV). The remaining classes are unsuitable for agricultural practices but suitable for pasture, plantation, forestry, wildlife habitat, and natural vegetation. This study reveals that land capability classes II and III occupy nearly half (49.94%) of the potential land area. Field observations and land use analysis indicate that good and moderately good LCC areas associated with fertile floodplains and intensive agricultural practices are being encroached upon by unplanned land utilization, especially rapidly expanding settlements and rubber plantations.